MATERNAL PLASMA CONCENTRATIONS OF THE SOLUBLE TUMOR NECROSIS FACTOR RECEPTOR 2 ARE INCREASED PRIOR TO THE DEVELOPMENT OF PREECLAMPSIA - Sibai, Baha (2009)
OBJECTIVE: Circulating tumor necrosis factor-alpha (TNF-α), a potent pro-inflammatory cytokine, capable of activating endothelial cells, as well as its soluble receptors (sTNF-R1 and sTNF-R2), is increased during overt preeclampsia, consistent with hypotheses that enhanced systemic inflammatory response and endothelial cell dysfunction are important in the pathophysiology of the preeclamptic syndrome. If so, such increases in levels should precede the onset of the disease. This study was designed to examine whether plasma concentrations of sTNF-R1 and sTNF-R2 are elevated prior to the onset of preeclampsia. METHODS: This was a retrospective biomarker study of stored maternal plasma from an NICHD preeclampsia prevention trial conducted in patients with risk factors for developing preeclampsia to test the effectiveness of low dose aspirin compared with placebo. The first sample was collected at 13–26 weeks’ gestation and the second at 24–28 weeks’ gestation. Serial sTNF-R1 and sTNF-R2 concentrations were assessed using sensitive and specific immunoassays in 1,004 patients in whom both samples were collected. RESULTS: The incidence of preeclampsia was 21.3% (214/1004). Median plasma levels of the sTNF-R2, but not sTNF-R1, were significantly higher at 13–26 weeks (sample 1) and at 24–28 weeks (sample 2) in patients who developed preeclampsia than in those who did not (sample 1: sTNF-R2: median 2,678 pg/ml, range 934–7,835 vs. median 2,535 pg/ml, range 1,022–13,000, p=0.02; sTNF-R1: median 936 pg/ml, range 449–3,239 vs. median 913 pg/ml, range 359–5,060, p=0.19). There was a significantly increased odds of preeclampsia for an increase in sTNF-R2 from sample 1 to sample 2 (OR=1.23 per 1,000 unit increase). Women in the fourth quartile of sTNF-R2 at 24–28 weeks, had a significantly increased adjusted odds of preeclampsia (OR=1.55, 95%CI=1.02–2.35, p=0.04), compared with women in the first quartile. This association, however, varied by treatment group (aspirin or placebo). No association was observed for sTNF-R1. The sensitivity and positive predictive values were low for sTNF-R2, as well as sTNF-R1. CONCLUSION: An increase in maternal plasma sTNF-R2 concentration precedes clinical manifestation of preeclampsia. These observations demonstrate that levels of proinflammatory cytokines rise well before development of overt disease and could be operative in the pathogenic mechanisms responsible for preeclampsia.